Działalność Rady Kapłańskiej Archidiecezji Krakowskiej za czasów Kardynała Karola Wojtyły - Dyduch, Jan (Prawo Kanoniczne, 1997)
While applying the program of the postconciliar renewal of the Cracovian Church, Cardinal Karol Wojtyła established the Priests’ Council which was to be the instrument of the renewal of priests’ life and ministry. This establishment was preceded by a period of preperation undertaken among the priests and the laity. The essential components of that preparation were the visitation of Our Lady of Jasna Góra Icon to every parish of the Cracow Archdiocese, and the priests’ regional conferences which deliberated on the local pastoral requirements in the light of the teaching of the Second Vatican Council. The Priests’ Council became the representation of the Archdiocesan clergy, also and advisory and informative body to the Archbishop, and a forum of his dialogue with the priests in general. In this way the Priests’ Council dealt with many question which occupied the clergy and systematically solved them by recommending constructive resolutions. These resolutions, approved by Cardinal Karol Wojtyła and by virtue of his authority, were then implemented with the assistance of the Priests’ Council.